Correlation of the Severity of Crowding Measured with ALD Analysis Against the Plaque Accumulation Using O’Leary Plaque Index: adescriptive study - Fauzia, Marlyana; Gayatri, Gita; Carolina, Dyah Nindita; Harsanti, Andriani; Zakaria, Myrna Nurlatifa (Padjadjaran Journal of Dental Researchers and Students, 2023)
ABSTRACT Introduction: Crowding is a condition where the length of the jaw arch is less than the length of the mesio-distal of the teeth summed. One of the methods to measure the severity of crowding is the Arch Length Discrepancy (ALD). Crowding may cause the plaque to accumulate more easily on the teeth surfaces, which can be measured by the O’Leary index. Thus, research will be done to see the impact of the crowding degree measured by the ALD analysis against the plaque accumulation measured by the O’Leary index. Methods: This research is a descriptive correlational study and the data collected is processed with Spearman’s rank correlation coefficient. 37 samples are acquired from patients of Periodontic Department in RSGM Unpad treated by co-assistant of FKG Universitas Padjadjaran year 2016 to 2019 from December 2020 to March 2021. Results: Based on the acquired data for ALD index, 2 people scored 5(ALD 0mm), 7 people scored 4(ALD 0mm until 3mm), 4 people scored 3(ALD -3mm until -5mm), 6 people scored 2(ALD -5mm until -10mm), 6 people scored 1(ALD below -10mm), 12 people scored -1(ALD above 0mm/positive). For O’Leary index, 1 person scored good, 8 people scored moderate, 11 people scored poor, 17 people scored very poor. Discussion: The data obtained was processed by Spearman’s rank correlation coefficient using the software SPSS Statistics 23 and resulted that the data obtained has a weak correlation of r = -0.352 and statistically significant by p = 0,033 (p<0,05). Conclusion: The result of the study shows that the effect of the severity of crowding as measured by the ALD index on plaque accumulation as measured by the O'Leary index is weak.KEY WORDS: crowding, plaque, ALD index, O’Leary index.Korelasi keparahan gigi berjejal diukur dengan analisis arch length discrepancy (ALD) terhadap akumulasi plak diukur dengan indeks plak o’leary: studi deskriptiABSTRAKPendahuluan: Crowding adalah suatu keadaan dimana lengkung rahang yang tersedia lebih sempit daripada jumlah panjang mesio-distal gigi geliginya. Salah satu cara mengukur tingkat keparahan crowding adalah dengan menggunakan Arch Length Discrepancy (ALD). Crowding dapat menyebabkan perawatan gigi lebih sulit sehingga plak mudah terakumulasi dan dapat diukur menggunakan analisis O’Leary. Pengaruh tingkat keparahan crowding terhadap akumulasi plak dapat diukur dengan analisis ALD terhadap indeks O’Leary. Metode: Penelitian ini merupakan penelitian deskriptif korelasional dan data yang terkumpul diolah dengan Uji Korelasi Spearman. Sampel penelitian berjumlah 37 data sekunder dengan rumus penentuan besar sampel minimal analisis korelatif dari pasien RSGM Unpad Departemen Periodonsia yang dirawat oleh koas FKG Universitas Padjadjaran tahun 2016 sampai 2019. Penelitian dilakukan pada bulan Desember 2020 sampai Maret 2021 di RSGM Unpad. Hasil: Berdasarkan data yang terkumpul untuk indeks ALD, terdapat skor 5 (pengukuran ALD 0 mm) sebanyak 2 orang, skor 4 (pengukuran ALD 0mm sampai -3mm)sebanyak 7 orang, skor 3 (pengukuran ALD -3mm sampai -5mm) sebanyak 4 orang, skor 2 (pengukuran ALD -5mm sampai -10mm) sebanyak 6 orang, skor 1 (pengukuran ALD dibawah -10mm) sebanyak 6 orang, dan skor -1 (pengukuran ALD lebih dari 0mm/positif) sebanyak 12 orang dan indeks O’Leary kategori baik 1 orang, sedang 8 orang, buruk 11 orang, dan buruk sekali 17 orang. Pembahasan: Data yang diperoleh dilakukan Uji Korelasi Spearman menggunakan software SPSS Statistik 23 dan didapatkan hasil yaitu data yang diperoleh berkorelasi lemah dengan nilai r = -0,352 dan signifikan secara statistik dengan nilai p = 0,033 (p<0,05). Simpulan: Hasil penelitian menunjukkan bahwa pengaruh tingkat keparahan crowding yang diukur dengan indeks ALD terhadap akumulasi plak yang diukur dengan indeks O’Leary berkorelasi lemah KATA KUNCI: crowding, plak, indeks ALD, indeks O’Leary